Land Tenure and Management: An Analytical Appraisal (The Pakistan Development Review, 2007)
The total area of Pakistan is 796101 sq. km (310,400 sq. miles) of which 414659 sq. km (160100 sq. miles) comprises mountainous terrain, narrow valleys and foot hills. The remaining 381442 sq. km (150300 sq. miles) consists of sand, deserts and flat gradational plains, the most important feature of which is Indus River Basin Plain with an area of about 311771 sq. km (123400 sq. miles). The area of principal hydrologic units is given in Table 1.